Sinergitas Yayasan Pembangunan Desa Sanur terhadap Masyarakat dalam Mencapai Good Governance - Ista Pradnyandhari, Anak Agung Made; Supriliyani, Ni Wayan; Sastra Wijaya, Komang Adi (CITIZEN CHARTER, 2021)
The Sanur Development Foundation is a pillar that maintains and accommodates the community empowerment program for the Sanur Traditional Village. This study aims to determine how the synergy that occurs between the Sanur Development Foundation and the Sanur Traditional Village community itself in realizing empowerment as a form of good governance. This research uses descriptive qualitative research methods with data collection techniques in the form of interviews, observation, and documentation. In conducting this research, the researcher used two indicators of synergy according to Covey, namely communication and coordination which shows that the synergy between the Sanur Development Foundation and the Sanur Traditional Village community itself has gone quite well, but therefore it is hoped that the established synergy will involve the community more from the planning stage to prevent irregularities and be more specific in meeting community needs. Keywords : Synergy, Community Empowerment, Society Participation, Good Governance